(3cJGH aj GdaQhSjI hGdQeis
(3ChdgG (B:s
(3jHJOF HGdHGH GdPi bHd HGH GdQjGVI Hbhdg (B: (3GdUHQ hPdc Cfg EPG cGf TOjO GdfaS Vjb GdeJfaS hJQOO GdfaS ai Lhag s
(3BNQgG (B:s
(3HGH GdQei HGdHfLcGf HNeS fTGHGJ eJhGdjGJ ddaGQS hGdQGLd ceG bGd GdTGaYi QMeg Gddg (B: (3EbHV Ydi GdeJf Hca cGdMLQ heO eOkG eSJbjekG eYJHQ hCSQY GdEWdGb ef ahb GdhJQ HYO GdhaGA hGdSchf hGdfXQ s
(3HgG fXGe GdJYbjHIs
(3jdjgG MQR eHGQc ddaQS hGdaGQSs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs